Update on the use of alitretinoin in treating chronic hand eczema - Pedram Ghasri; Noah Scheinfeld (Dove Medical Press, 2010)
Pedram Ghasri1, Noah Scheinfeld21University of California, Irvine School of Medicine, Irvine, CA, USA; 2Department of Dermatology, Columbia University, School of Medicine, New York, USAAbstract: Chronic hand eczema is a debilitating dermatological condition with significant economic, social, and functional impacts. To date, conventional treatments such as topical corticosteroids, phototherapy, and systemic immunosuppressants have yielded disappointing results, owing to either a lack of efficacy or significant adverse events. Oral alitretinoin (9-cis-retinoic acid) is a unique panagonist retinoid with immunomodulatory and anti-inflammatory activity that has emerged as a novel treatment for chronic hand eczema. Several large-scale clinical studies have demonstrated oral alitretinoin’s high efficacy rate of 28% to 89%, its safe tolerability profile, and its positive impact on quality of life, validating it as a therapeutic option for patients with severe chronic hand eczema refractory to standard treatment.Keywords: hand eczema, alitretinoin, 9-cisretinoic acid